Fossil Fuel Refinery Resuscitation Policy and the Implications for the Clean Energy Transition Plan in Nigeria - Adeforiti, Rotimi (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
The Nigerian government’s planned resuscitation of fossil fuel refineries is expected to impact the country’s clean energy transition plan by influencing public acceptance of that policy. It remains unclear how the government will bridge this gap between fossil fuel revival and clean energy commitments. This study examines the drivers behind Nigeria’s refinery resuscitation policy and the policy’s implications for the nation’s clean energy transition. The analysis is grounded in Choice Theory, operating on the premise that behavior (including policy decisions) originates from within and is driven by attempts to satisfy basic needs, meaning policymakers choose their actions based on those needs[1]. The research method is a semi-systematic review (SSR), for which 20 peer-reviewed journal articles (published 2015–2024) were purposively selected. The findings indicate that several factors sustaining fossil fuel use globally are encouraging Nigeria’s refinery revival. These factors include the persistent international market demand for fossil fuels, the perceived non-substitutability of fossil fuels in economic and military contexts, supportive government policies, and the state’s failure to secure sufficient clean energy investment. Reviving refineries implies a continued supply of and demand for fossil fuels as primary energy sources in the near term. The study concludes that each country should contextualize its energy transition strategy according to its unique circumstances.